2018
DOI: 10.1016/j.ijhydene.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Explosion venting of hydrogen-air mixtures from a duct to a vented vessel

Abstract: Experiments were conducted on the vented explosion of hydrogen-air mixtures from a 1.5-m-long duct to a vented cylindrical vessel to investigate the effects of vent burst pressure and an obstacle in a duct on the process of explosion venting. Turbulent pressure oscillation owing to a pressure wave moving back and forth in a duct and vessel was observed for unvented explosions. For explosion venting from a duct to a vessel, the maximum reduced overpressure increased with an increase in the vent cover thickness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Vented explosion of hydrogen air mixtures through a 0.5-m-long duct was investigated and it was found that the use of the relief duct significantly increased the explosion overpressure compared with the cases without the duct for hydrogen concentration ranging from lean to rich [25]. The experiments on explosion venting of hydrogen-air mixtures from a 1.5-m-long duct to a vented cylindrical vessel showed that maximum reduced overpressure first increased and then decreased with an increase in hydrogen concentration [26].…”
Section: Ponizy and Leyermentioning
confidence: 99%
“…Vented explosion of hydrogen air mixtures through a 0.5-m-long duct was investigated and it was found that the use of the relief duct significantly increased the explosion overpressure compared with the cases without the duct for hydrogen concentration ranging from lean to rich [25]. The experiments on explosion venting of hydrogen-air mixtures from a 1.5-m-long duct to a vented cylindrical vessel showed that maximum reduced overpressure first increased and then decreased with an increase in hydrogen concentration [26].…”
Section: Ponizy and Leyermentioning
confidence: 99%
“…Over the recent years, the explosive characteristics of combustible gas with barriers have been extensively studied experimentally. 7 , 8 These studies focused on the shape, 9 15 blockage ratio, 16 19 location, 20 23 number, 24 26 spacing, 27 , 28 and fuel concentration. 29 33 Further, experiments have been conducted to obtain the explosive pressure parameters and flame transmission characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…When inflammable substances escape from gas cookers in households or professional equipment at industrial sites, there an explosive and flammable mixture appears [24][25][26][27]. The explosive-pressure-dynamic parameter-calculation program that we developed accurately describes the explosive-load generation process in premises with no protective structures (PS), as well as in EVS-equipped premises.…”
Section: Introductionmentioning
confidence: 99%